The Use of Flashcard Media for the Preservation of language Temanggungan at Madrasah Ibtidaiyah Elpist Temanggung - Mu'anayah, Nur Alfi; Chailani, Muchammad Iqbal; Febyola, Farach Feby; Rahmawati, Dwi Indah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research focused on the low level of understanding of grade 3 students at MI Elpist Temanggung Central Java towards the Javanese language in Temanggung dialect or Basa Temanggungan. It was caused by the dominance of the use of Indonesian in everyday life and was reinforced by the influence of language through digital media. Another contributing factor was the negative perception of the Temanggung dialect, which needed to be more modern, thus affecting students' motivation to learn and use this language. The research method used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to develop flashcard-based learning media containing local wisdom. This flashcard integrated local cultural elements such as tembang dolanan, which not only served to improve vocabulary understanding but also instilled Temanggung cultural values. The research results showed that the use of flashcards significantly increased students' interest and understanding of Basa Temanggungan, especially in tembang dolanan materials such as